To the Outermost Parts of the Galaxy: Imagination’s Puissance in Decolonizing International Law - Rafsi Azzam Hibatullah Albar (Mimbar Hukum, 2026)
Abstract This paper examines how imagination, despite its historical instrumentalization as a colonial methodology in international law as revealed in Koskenniemi’s To the Uttermost Parts of the Earth, can be repurposed as a decolonial tool. By drawing a temporal analogy, it first introduces imagination's role in the early European international legal thought by exploring Koskenniemi’s examples of bricolage alongside Anghie’s ‘dynamic of difference’ to underscore the need for disenchantment. It then looks into present-day counter-narratives emerging from Global South imaginations encapsulated in the third world approaches to international law or the TWAIL movement that challenge the colonial ever-present. Finally, it advocates for speculative thinking drawn from various sources as a means of envisaging alternative futures for international law, with particular emphasis on scientific and other types of fictions . The paper concludes by arguing for a structured yet creative decolonial imagination agenda that can help overcome the persistence of colonial legacies in international law while maintaining sufficient space for revolutionary thinking about world order. Abstract Makalah ini mengkaji bagaimana imajinasi, meskipun secara historis telah diinstrumentalisasi sebagai metodologi kolonial dalam hukum internasional sebagaimana ditunjukkan oleh Koskenniemi dalam To the Uttermost Parts of the Earth, dapat digunakan kembali sebagai alat dekolonial. Dengan menggunakan analogi temporal, makalah ini pertama-tama membahas peran imajinasi dalam pemikiran hukum internasional Eropa awal melalui contoh-contoh bricolage yang diuraikan oleh Koskenniemi serta konsep dynamic of difference dari Anghie untuk menegaskan pentingnya proses disenchantment (pembongkaran ilusi atau pesona kolonial). Selanjutnya, makalah ini menelaah narasi tandingan kontemporer yang lahir dari imajinasi Global Selatan, sebagaimana tercermin dalam gerakan Third World Approaches to International Law (TWAIL), yang menantang keberlangsungan kolonialisme dalam hukum internasional masa kini. Pada akhirnya, makalah ini mengadvokasi pemikiran spekulatif yang bersumber dari berbagai tradisi sebagai sarana untuk membayangkan masa depan alternatif bagi hukum internasional, dengan penekanan khusus pada fiksi ilmiah dan bentuk-bentuk fiksi lainnya. Makalah ini menyimpulkan bahwa agenda imajinasi dekolonial yang terstruktur namun tetap kreatif dapat membantu mengatasi keberlanjutan warisan kolonial dalam hukum internasional, sembari mempertahankan ruang yang memadai bagi pemikiran revolusioner mengenai tatanan dunia.